Mira's last dance : a fantasy novella in the world of the five gods - Bujold, Lois McMaster (Bujold, Lois McMaster. World of the five gods: Penric and Desdemona, 2018)
In this sequel to the novella Penric's Mission, the injured Penric, a Temple sorcerer and learned divine, tries to guide the betrayed General Arisaydia and his widowed sister Nikys across the last hundred miles of hostile Cedonia to safety in the Duchy of Orbas. In the town of Sosie the fugitive party encounters unexpected delays, and even more unexpected opportunities and hazards, as the courtesan Mira of Adria, one of the ten dead women whose imprints make up the personality of the chaos demon Desdemona, comes to the fore with her own special expertise.